2021
DOI: 10.17344/acsi.2020.6513
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics Transfer Across the Membrane: Reproducing Octanol-Water Partition Coefficients by Solvent Reaction Field Methods

Abstract: Local anesthetics are one of the most widely used drug classes in clinical practice. Like many other biological molecules, their properties are altered depending on their protonation status, which is dependent on the pH of the environment. We studied the transport energetics of seven local anesthetics from the extracellular fluid across the biological membrane to the axoplasm in order to understand the effect of pH value on their efficacy and other pharmaco-dynamic roperties. In this we applied three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Calculations of pKa values are very demanding and can serve as one of the strictest tests for the efficiency of various solvation models (Kavcic et al, 2021;Repicˇet al, 2014;Warshel, 1981). Our results show that the calculated pKa value of dopamine o-quinone (pKa calc = 8.73) is in good agreement with the experimental pKa value of dopamine (pKa exp = 8.86) (Berfield et al, 1999) showing that the SMD reaction field solvation model with M06/Def2-TZVPP level of theory is sufficiently accurate.…”
Section: The Pka Values Of Metal Cation-dopamine O-quinone Complexessupporting
confidence: 55%
“…Calculations of pKa values are very demanding and can serve as one of the strictest tests for the efficiency of various solvation models (Kavcic et al, 2021;Repicˇet al, 2014;Warshel, 1981). Our results show that the calculated pKa value of dopamine o-quinone (pKa calc = 8.73) is in good agreement with the experimental pKa value of dopamine (pKa exp = 8.86) (Berfield et al, 1999) showing that the SMD reaction field solvation model with M06/Def2-TZVPP level of theory is sufficiently accurate.…”
Section: The Pka Values Of Metal Cation-dopamine O-quinone Complexessupporting
confidence: 55%
“…In a similar sense, this also holds for aqueous phases with different pH values. Partition coefficients stemming from experiments 30 or reaction field computations 31 can be used in a thermodynamic model to compute the pH-dependent distribution of anesthetics in detail. 32 While we qualitatively discuss pH effects, the main focus of our work is on the transfer dynamics and its time scale.…”
Section: Free Energy Surfacementioning
confidence: 99%
“…The effects of solvation were considered by applying the universal solvation model (SMD) ( Marenich et al, 2009 ). We chose the SMD solvation model because, in our previous studies, it was found to be the most accurate in reproducing the solvation effects of local anesthetics and other organic molecules ( Umek, 2020 ; Kavčič et al, 2021a ; Umek, 2022 ). In this study, we considered two solvents: water with a dielectric constant of 78.30 and n-octanol with a dielectric constant of 9.86.…”
Section: Methodsmentioning
confidence: 99%